The Effect of Rainfall Changes on Maize Production in Southeast Sulawesi in 1990-2024 - Hesty Sukma Dewi; Sitti Hajrah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Climate change, reflected in rainfall fluctuations, has become a significant challenge to the sustainability of maize production systems in the tropics. As one of the nation's strategic commodities, maize is highly vulnerable to climatic disturbances, especially changes in rainfall that affect soil water availability, pest and disease distribution, and yield quality and quantity. Previous research shows that rainfall that does not match the physiological needs of plants can reduce productivity, either due to extreme drought or excessive rain during critical growth phases. This study empirically analyzes the impact of rainfall on maize production in Southeast Sulawesi Province from 1990 to 2024. The research was conducted in February and March 2025, using a quantitative approach with a simple regression analysis method. The data used are secondary data on corn production (in tons) and annual rainfall (in mm), obtained from the Central Bureau of Statistics and the Agriculture Office of Southeast Sulawesi Province. The independent variable in this study is rainfall, while the dependent variable is maize production. The analysis results indicate that rainfall has a positive and significant influence on maize production, with a regression coefficient of 26.418 and a significance level of 0.037. Although the Adjusted R Square value is only 0.099, this result confirms that rainfall is one of the crucial factors contributing to the variability of maize yields from year to year. This finding provides an essential basis for designing evidence-based agricultural adaptation strategies in response to future climate change challenges.